Characterization of Lipopeptide Biosurfactants Produced by Bacillus licheniformis MB01 from Marine Sediments - Chen, Yulin; Liu, Shiliang A.; Mou, Haijin; Ma, Yunxiao; Li, Meng; Hu, Xiaoke (Frontiers in Microbiology, 2017)
Antibiotic resistance has become one of the world’s most severe problems because of the overuse of antibiotics. Antibiotic-resistant bacteria are more difficult to kill and more expensive to treat. Researchers have been studied on antibiotic alternatives such as antimicrobial peptides and lipopeptides. A bacteriostatic functional bacteria MB01 producing lipopeptides was isolated from the Bohai Sea sediments, which had been identified as Bacillus licheniformis by the morphological, physiological and biochemical identification and 16s rDNA sequence. The lipopeptides produced by MB01 were determined to be cyclic surfactin homologs by LC-ESI-MS structural identification after crude extraction and LH-20 chromatography. [M+H]+ m/z 994, 1008, 1022, 1036 were all the characteristic molecular weight of surfactin homologs. CID analysis revealed that the molecular structure of the lipopeptides was Rn-Glu1-Leu/Ile2-Leu3-Val4-Asp5-Leu6-Leu/Ile7. The lipopeptides showed well resistance to UV light and the change of pH and temperature.